2010
DOI: 10.1007/s00415-010-5512-9
|View full text |Cite|
|
Sign up to set email alerts
|

The epidemiology of CuZn-SOD mutations in Germany: a study of 217 families

Abstract: We screened 217 patients from Germany (n = 213), Austria (n = 2) and Switzerland (n = 2) with a positive family history for amyotrophic lateral sclerosis (ALS) for mutations in the copper/zinc superoxide dismutase (SOD1) gene. We found that 13% of the families tested carried mutations. By analyzing inheritance, we detected a clear-cut co-segregation in 5 of the 28 families; however, in two families with an established mutation, co-segregation was absent. In Germany, the R115G mutation is comparatively frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…This aggressive phenotype could be explained by a high functional importance of the altered amino acid within the SOD1 enzyme, which confers high toxicity to the mutant protein. This is in line with the phenotype already described by Rabe and coworkers, characterized by a very rapid disease progression and, in some cases, a late age at onset of the disease (Rabe et al, 2010). A strong genotypephenotype correlation has been proved for a minority of SOD1 mutations (Del Grande et al, 2011).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This aggressive phenotype could be explained by a high functional importance of the altered amino acid within the SOD1 enzyme, which confers high toxicity to the mutant protein. This is in line with the phenotype already described by Rabe and coworkers, characterized by a very rapid disease progression and, in some cases, a late age at onset of the disease (Rabe et al, 2010). A strong genotypephenotype correlation has been proved for a minority of SOD1 mutations (Del Grande et al, 2011).…”
Section: Discussionsupporting
confidence: 73%
“…Until now, the mutation identified in our patient, has not previously been described in the Italian or other populations and has not been reported in the ALSOD database (http://alsod.iop.kcl.ac.uk). A different heterozygous point mutation, that leads to a different amino acid substitution (arginine to glycine) at position 115 (R115G) was identified by Kostrzewa et al (1994) and it has been reported to be the most frequent SOD1 mutation in German fALS (Rabe et al, 2010). Arginine at codon 115 is a high evolutionary conserved amino acid in vertebrates, invertebrates, higher plants, and yeast as predicted by Clustal W2 software (http://www.ebi.ac.uk/Tools/ clustalw2/).…”
Section: Discussionmentioning
confidence: 99%
“…Since SOD catalyzes production of H 2 O 2 , which is also a powerful oxidant, some of the studies used SOD in combination with H 2 O 2 metabolizing antioxidants such as catalase. Mutations in sod gene, its deficiency, and certain SOD genotypes are proposed to directly correlate with several disorders such as amyotrophic lateral sclerosis [67]. Thaler et al proposed this to be the reason why vegetarians show lower rates of several types of cancer and chronic cardiovascular diseases as compared with omnivores [68].…”
Section: Importance and Applicationsmentioning
confidence: 98%
“…Treatment of inflammation in animals [86,93] Clinical purposes and specific applications in the food industry systems [3,58,66,67,70,85,87,93,94] Preservation of perishables like vegetables [88] Preservation of biologicals, like organs for transplantation and sperms [89,90] Reduction in tobacco and alcohol-induced damage [91] Biosensor for O2 − [92] Cosmetics for the protection of the skin [3,30] Prevent alcohol-induced hangover [95] Removal of Amadori and Maillard products [96] Mutagenicity testing [97,98] elicited these effects by scavenging the inflammatory superoxide anion [73]. Elevated SOD activity can be therapeutically useful by protecting against oxidative stress-induced neurotoxicity.…”
Section: Applications Referencementioning
confidence: 99%
“…Various clinical trials have been carried out in humans to hamper and control the ROS by supplementation of SOD and thereby to overcome such diseases. The proliferation of amyotrophic lateral sclerosis (ALS) have been reported due to the mutation in sod gene or its deficiency in human [7]. The expression fold of SOD can be optimized epigenetically in diet, which suppressed the CpG methylation in promoter and thus induced the expression fold of Mn SOD in the vegetarian group when compared with the omnivorous group.…”
Section: Pharmaceutical Applications Of Sodmentioning
confidence: 99%